Proyecto de inversión para la optimización de los servicios del hotel “Ames” cantón Buena Fe, período 2015-2017 - Lara Rodríguez, Karla Kirlenkey (2015)
This project entitled "Investment project for the optimization of the Hotel" AMES "Buena Fe Canton, period 2015-2017", was conducted in order to contribute to the growth of the company and all those who depend on it directly or indirectly, to investigate the specific objectives were related to market research to determine the level of satisfaction achieved by customers, the technical study to determine the favorable conditions of the hotel and the economic and financial study to improve the profitability of the establishment question. The project contains theoretical foundation where the main topics and subtopics that surround the topic under study, supported in investigations of several authors are described. The methodology consists of the types of field research and documentary, while the methods used were; deductive, inductive, analytical and observation, data collection sources were formed by primary and secondary, primary found in the surveys and interviews and secondary sources correspond to literature. The results allowed us to achieve the objectives, in terms of market research, 64% of customers surveyed said that services offered by the "AMES" Hotel is very good and that the reasons for their stay is for work and holidays , facilities are adequate but need new equipment to some rooms. The technical study showed that the hotel is geographically located in an area of affluence, it has a capacity of 81 people to provide housing, but requires more advertising to attract customers. The economic and financial study shows an investment of $28,195.60, income range between $102.405,60 and $156.606,72, while the profit for the year 2017 will reach $89.386.90, the internal rate of return is 142% The net present value of the exercise is $104.799,53, the investment will recover in 1 year 6 months.